PERANAN PARTAI POLITIK DALAM DEMOKRASI DI INDONESIA - Muhammad Jafar AW (Universitas Sultan Ageng Tirtayasa, 2015)
The role of political parties is affecting the condition and future of the nation, because through the results of the election will produce a new leadership , electedthrough a general election . Meaning of democratization in the life of the nation is onewith a general election that will send the nation to the leadership and the newgovernment , in the hope , citizen want the new government will provide improvementsin all areas of life . Thus, the policy change of the state and nation , not lose frompolitical parties role’s that fill with people's democratic party with a vision and missionof the Party which varies in accordance with the ideology